2005
DOI: 10.1001/jama.294.14.1782
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of End-stage Renal Disease in Patients With Type 1 Diabetes

Abstract: Context End-stage renal disease (ESRD) is one of the most severe complications of type 1 diabetes. Yet, data on patients' risk of developing ESRD are sparse. Objectives To estimate the long-term risk of developing ESRD and to assess how age at diagnosis of diabetes, time period of diagnosis, and sex affect the risk. Design, Setting, and Patients A cohort of all patients younger than 30 years diagnosed as having type 1 diabetes in Finland in 1965-1999 (n=20 005) was identified from the Finnish Diabetes Register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
147
6
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(180 citation statements)
references
References 27 publications
19
147
6
7
Order By: Relevance
“…However, extrapolation of our results to all patients with type 1 diabetes showed that they incur more than 10% of all outpatient prescription medication costs. Although the incidence of ESRD has decreased [24,25], the number of ESRD patients is still increasing in Finland as well as worldwide due to the increasing incidence of diabetes, especially type 2 diabetes [26]. From this point of view, our findings together with previous studies highlight the importance of prevention, early diagnosis and intensive treatment of chronic kidney disease.…”
Section: Discussionsupporting
confidence: 61%
“…However, extrapolation of our results to all patients with type 1 diabetes showed that they incur more than 10% of all outpatient prescription medication costs. Although the incidence of ESRD has decreased [24,25], the number of ESRD patients is still increasing in Finland as well as worldwide due to the increasing incidence of diabetes, especially type 2 diabetes [26]. From this point of view, our findings together with previous studies highlight the importance of prevention, early diagnosis and intensive treatment of chronic kidney disease.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that age at onset of type 1 diabetes has an effect on the risk of microvascular complications, including diabetic nephropathy [1,2] and diabetic Electronic supplementary material The online version of this article (doi:10.1007/s00125-015-3816-0) contains peer-reviewed but unedited supplementary material, which is available to authorised users. proliferative retinopathy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Conditional probabilities for end-stage renal disease in people with microalbuminuria [13] and for death in people with end-stage renal disease were based on published literature.…”
Section: Microalbuminuria and End-stage Renal Diseasementioning
confidence: 99%